Pensions in aging Asia and the Pacific: Policy insights and priorities - Rafal Chomik; Philip O'Keefe; John Piggott (Asian Development Bank (ADB), 2024)
Asia and the Pacific has the most diverse regional pension landscape globally. Yet the region's pension systems are facing common challenges as they attempt to expand coverage, and ensure adequacy and fairness, while maintaining fiscal sustainability. We review the structures and performance of pension systems across Asia and the Pacific. Most remain characterized by low contributory coverage, social pensions with inadequate benefits and often low (or no) coverage, and informal sector schemes with modest traction to date. They are also characterized by gender inequities, lack of policy flexibility and attention to labor incentives, and underdeveloped governance structures. The paper makes proposals for addressing these challenges through an expanded role for social pensions with inclusive targeting, reformed contributory schemes, ongoing innovations for the informal sector and women, and enhanced reliance on technology.
Keywords: H55; N35; J18; 330; pension; Asian pension; social protection in Asia; means tested pension